" La violencia intrafamiliar vulnera los derechos constitucionales del buen vivir" - Romero Abril, Gloria María (2013)
This thesis is a critical step for obtaining a law degree from the Courts of the Republic of Ecuador, is sustained and developed in six chapters, pointing out the theme "Family Violence infringe the right to a good life ", was based on research conducted in various reference texts, laws, our treaties and conventions and Comparative law, asked what allowed me to objectively carry out this legal research. The background analysis, Doctrinal and Comparative Law, Law and the issue and the problem posed, served to hypothesize, general and specific objectives, which allowed for adjusted posed methods, field research by surveying citizens and Quevedo Canton citizen, so have a database that was used to justify the hypothesis. The general and specific objectives were justified which determined the conduct and approach of the proposal which seeks to amend the Law on Violence Against Women and Family in the changes that will arise to the good life a new way of life and progress of families, looking aside domestic violence as an appropriate means of damaging and breaking up the family. The social impact of the proposed reform beneficiaries will be especially women who are most affected by domestic violence.